Cover Picture: Identification and Optimization of the First Highly Selective GLUT1 Inhibitor BAY‐876 (ChemMedChem 20/2016). (19th October 2016) - Siebeneicher, Holger; Cleve, Arwed; Rehwinkel, Hartmut; Neuhaus, Roland; Heisler, Iring; Müller, Thomas; Bauser, Marcus; Buchmann, Bernd
Abstract : The front cover picture shows a railway track symbolizing the transport of glucose as energy supply into a tumor cell by the GLUT1‐transporter. This import through the GLUT1‐transporter is blocked by a quinolinedicarboxamide, a compound series inhibiting the glucose transport in a competitive, reversible, and very selective manner against GLUT2, 3, and 4. The structure–activity relationship (SAR) and in vitro pharmacokinetics (PK) of the quinolinedicarboxamides presented in this work ended in the shown lead compound BAY‐876, a chemical probe with an appropriate in vivo PK profile for efficacy studies. More information can be found in the Full Paper by Bernd Buchmann et al. onpage 2261 in Issue 20, 2016 (DOI:10.1002/cmdc.201600276 ).